2014
DOI: 10.3109/19401736.2014.913141
|View full text |Cite
|
Sign up to set email alerts
|

Determination and analysis of complete mitochondrial genome sequence of Peking duck ( Anas platyrhychos )

Abstract: The complete mitochondrial genome (mtDNA) of Peking duck (Anas platyrhychos) was determined. The entire genome was 16,604 bp in length. Similar to the typical mtDNA of vertebrates, it contained 37 genes (13 protein-coding genes, 2 rRNA genes, 22 tRNA genes) and a non-coding region (D-loop). The characteristics of the mitochondrial genome was analyzed and discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Sixteen pairs of primers ( S1 Table ) were designed using Primer Premier 5.0 [ 70 ] based on the mito-genomes of Anas platyrhynchos (EU009397) [ 71 ], A . falcata (NC_023352) [ 72 ], Anser fabalis (NC_016922) [ 27 ], Dendrocygna javanica (NC_012844) [ 73 ] and Anseranas semipalmata (NC_005933) [ 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sixteen pairs of primers ( S1 Table ) were designed using Primer Premier 5.0 [ 70 ] based on the mito-genomes of Anas platyrhynchos (EU009397) [ 71 ], A . falcata (NC_023352) [ 72 ], Anser fabalis (NC_016922) [ 27 ], Dendrocygna javanica (NC_012844) [ 73 ] and Anseranas semipalmata (NC_005933) [ 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nucleotide sequences result of 469 nucleotide (nt) from Magelang, Tegal, Mojosari, Bali and Alabio ducks were administered for SNP analysis and nucleotide frequency. To determine polymorphism, the nucleotide sequences of local ducks in this research were compared with those of Anas platyrhynchos from (Gen Bank number HM 010684.1) as the standard (Tu et al, 2009). For instance, difference spotted in C16223T duck sample indicating C different nucleotide on nucleotide position 16223 by standard; in contrast, the sample indicated T. The result obtained could be used as genetic marker in Indonesian local ducks.…”
Section: Dna Primer Design and Amplification Using Pcrmentioning
confidence: 99%
“…Evolution analysis was performed in MEGA5 [2]. Tu et al (2009) reported that nucleotide composition in Beijing duck (Anas platyrhychos) in complete mitochondria genome was A = 29.19%, T/U = 22.20%, C = 32.81% and G = 15.80%. Different nucleotide frequency obtained was assumed due to different length and position of nucleotide used in data analysis.…”
Section: Snp Analysis On Mtdna D-loop Region Of Indonesia Local Ducks...mentioning
confidence: 99%
See 1 more Smart Citation